The Experiences of Nurse Educators in Developing and Implementing Concurrent Enrollment Associate Degree in Nursing–Bachelor of Science in Nursing Programs. - Hawkins, Janice E.; Chard, Robin; Seibert, Diane (Teaching & Learning in Nursing, 2018)
There is a critical shortage of bachelor of science-prepared nurses. Efficient pathways for bachelor of science completion, such as concurrent enrollment associate degree-to-bachelor of science programs, are needed to meet workforce demands. This article shares findings from a study of the experiences of nurse educators in developing and implementing concurrent enrollment in associate degree-to-bachelor of science programs. Detailed accounts of their experiences may facilitate an understanding of the process and assist educators in implementing similar programs.